PELATIHAN PEMBUATAN REAGEN KIMIA UNTUK PRAKTIKUM IPA SMP DAN IMPLEMENTASINYA DALAM KEGIATAN PEMBELAJARAN BAGI GURU IPA, LABORAN DAN SISWA SMP - Eny Hartadiyati; Maria Ulfah; Praptining Rahayu; Lussana Rossita Dewi (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2011)
Abstract Based on the survey, SMP Negeri 4 Semarang had many parrarel classes that it had?é?á 3 hours/week for science subject. To support it, this school was equipped by having a natural sciences labolatory. Actually, the teaching and learning process at the labolatory has been done well, but it needed to develop. Thus, they still need to buy?é?á reagent?é?á in chemistry store or health labolatory to help teaching natural sciences on practical work. Therefore, that chemistry reagent was not in new condition. Chemistry reagent which was kept too long in a storage place would decrease its ?é?áquality, then it will reduce the validation result if it is used for experiment on practical work.?é?á This case was caused by the teachers whose lack of skills in using the practical tools and understanding the function of these tools and materials. Then, we need a management in how to use practical work especially chemistry materials and reagent. The target of this program was natural sciences teachers, labolatory assistants and students of SMP Negeri 4 Semarang. The output result for this program was chemistry reagent and a set of equipment. This training makes the teachers and labolatory assistants more competent in providing chemistry reagent for natural sciences practical work autonomously. Key words: chemistry reagent, natural sciences teachers, labolatory assistants.